2015
DOI: 10.1002/hyp.10759
|View full text |Cite
|
Sign up to set email alerts
|

Effective groundwater-surface water exchange at watershed scales

Abstract: Coupled groundwater–surface water (GW–SW) models are capable of simulating complex hydrological systems when used at fine resolutions. However, properly characterizing bulk GW–SW fluxes for either coarsely resolved integrated models or basin‐discretized surface water models remains a challenge. Loss of subgrid detail, while beneficially decreasing computational cost, leads to a decrease in model accuracy as scale effects become important. Ideally, coarse low‐resolution models should be informed by expected sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Permeability versus depth plots for both EPM rock mass and FZs were produced. In previous studies, it has been found that power law functions were appropriate to represent many hydrological processes (Cardenas, 2008; Harman et al., 2009; Rupp & Selker, 2005; Selker et al., 1999; Snowdon & Craig, 2015) so a power law function (Equation 4) was used. log10(k)=a×db where k is permeability [m 2 ], d is depth [m], a is a fitting parameter, and b is a fitting parameter.…”
Section: Methodsmentioning
confidence: 99%
“…Permeability versus depth plots for both EPM rock mass and FZs were produced. In previous studies, it has been found that power law functions were appropriate to represent many hydrological processes (Cardenas, 2008; Harman et al., 2009; Rupp & Selker, 2005; Selker et al., 1999; Snowdon & Craig, 2015) so a power law function (Equation 4) was used. log10(k)=a×db where k is permeability [m 2 ], d is depth [m], a is a fitting parameter, and b is a fitting parameter.…”
Section: Methodsmentioning
confidence: 99%